Cecil Rhodes, the Glen Grey Act, and the labour question in the politics of the Cape Colony - Thompson, Richard James (Rhodes University, Faculty of Humanities, Department of History, 1991)
Chapter One: The provisions of the Glen Grey Act of 1894 are summarised. The memoirs of contemporaries are discussed and the historical literature on the Act from 1913 to the present is surveyed. The likelihood of the land tenure provisions of the Act forcing the people of Glen Grey (or the people of other districts that came under the operation of the Act) to seek employment is noted. It is evident that there is an increasing emphasis in the literature on labour concerns rather than on the disenfranchising effects and local government provisions of the Act. It is often assumed that the labour force generated by the Act was meant for the Transvaal gold mines. Chapter Two: The relevance of the labour needs of the Indwe collieries is investigated. These mines lay adjacent to Glen Grey and might have been expected to draw their labour thence if the Act had been effective. Rhodes, the author of the Act and prime minister of the Cape, had bought shares in the collieries for De Beers shortly before the Act was passed, which made a possible connection more intriguing. No causal link between De Beers' interests and the Act could be demonstrated; nor do the collieries seem to have employed many people from Glen Grey. Chapter Three: Examines the Cape colonists' complaints about shortage of labour from 1807 to the eve of the Glen Grey Act, and investigates various official measures to promote the labour supply. The Glen Grey Act was not the first labour measure passed at the Cape, and it seems likely, therefore, that the labour needs of the Cape, rather than the Transvaal, were uppermost in the minds of those responsible for the Act. Chapter Four examines Rhodes's political position in the 1890s and shows him to be increasingly dependent on the parliamentary support of the Afrikaner Bond to stay in office. Since the Bond was an agricultural interest group it seems likely that labour for Cape farms, rather than Transvaal gold mines, was what the Act was supposed to provide. With that Rhodes could readily agree, since he wanted to promote the agricultural development of the Cape. However, the Bond wanted to be able to buy land in Glen Grey (and other district in which the Act was proclaimed). Rhodes wanted to keep such districts as 'reservoirs of labour' so he could not give the Bond all of what they wanted, i.e. Glen Grey titles to be alienable. His manoeuvring to keep the Bond supporting the Bill while not making the land readily salable is described. (In the end the land was alienable with the consent of the government -- consent that a Rhodes ministry would not give, but that another might.) Rhodes's desire to obtain the administration of Bechuanaland for his Chartered Company, and his need therefore to reassure the Colonial Office and humanitarian opinion that he could be trusted to rule over blacks, are pointed out as other possible motivations for the Act, which Rhodes tried hard to present as an enlightened piece of legislation. The course of the Act through the Cape parliament, and the opposition of Cape liberals to the Act, is described. Chapter Five: The mentalité of the Cape colonists as regards race, liquor, land tenure and other political issues is described. Chapter Six: The reaction to the Act of Cape blacks and sympathetic whites, British humanitarians and the Colonial Office is described. The contemporary concern with reserving land for blacks is noted, as well as concern over the morality of economically coerced labour. This is in contrast to the modern concentration on labour almost to the exclusion of other issues in regard to the Glen Grey Act. The unsuccessful efforts of Cape blacks and British humanitarians to have the imperial government veto the Act are described. Rhodes's influence over the Colonial Office is described.
Keywords: Rhodes, Cecil, 1853-1902; Labor policy -- South Africa -- History; Labor supply -- South Africa -- History; Black people -- Employment -- South Africa -- History; Cape of Good Hope (South Africa) -- History -- 1872-1910; Cape of Good Hope (South Africa) -- Politics and government -- 1872-1910